Impacts of National and Local Chapters of 500 Women Scientists. - Dapkey, Tanya; Anantapantula, Saranya; McBride, JoEllen (Transactions of the American Philosophical Society, 2025)
The article discusses the impacts of the organization 500 Women Scientists (500WS) on promoting equity and representation for women in STEMM (Science, Technology, Engineering, Mathematics, and Medicine) fields. Despite progress, women remain underrepresented, particularly in senior roles, prompting the formation of 500WS in response to societal challenges and the need for advocacy. The organization has established local chapters, known as "pods," which have grown to over 550 worldwide, engaging in initiatives that include mentorship, public outreach, and policy advocacy to support underrepresented groups in science. Key programs such as the "Request a Woman in STEMM" database and Wiki-a-thons aim to enhance visibility and representation of women scientists, while ongoing efforts focus on institutional accountability and community engagement to foster a more inclusive scientific environment.